2021
DOI: 10.1002/eng2.12421
|View full text |Cite
|
Sign up to set email alerts
|

Control of dissolved oxygen significantly increases the yield of skin‐derived Schwann cells during expansion in stirred suspension bioreactors

Abstract: Peripheral nerve and spinal cord injuries affect millions of people worldwide often leading to lifelong disability and pain. Cell therapy using autologous Schwann cells are currently being investigated for the treatment of these injuries and are showing great potential. In particular, skin-derived Schwann cells offer a non-invasive option for highly therapeutic cells that have been shown to regenerate tissue and restore function. However, it is estimated that for an effective therapy, hundreds of millions of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The efficient and reproducible inoculation results achieved lead to high overall reproducibility in the expansion of skin-SCs between both bioreactor runs. By using bioreactors with computer-controlled set points, and maintaining each bioreactor at the same values, not only are higher growth kinetics and cell densities achieved, but there is less variability between runs compared to expansion in uncontrolled spinner flasks [ 34 ]. The culture parameters were maintained within a tight window around each set point allowing for the best conditions to expand the skin-SCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficient and reproducible inoculation results achieved lead to high overall reproducibility in the expansion of skin-SCs between both bioreactor runs. By using bioreactors with computer-controlled set points, and maintaining each bioreactor at the same values, not only are higher growth kinetics and cell densities achieved, but there is less variability between runs compared to expansion in uncontrolled spinner flasks [ 34 ]. The culture parameters were maintained within a tight window around each set point allowing for the best conditions to expand the skin-SCs.…”
Section: Discussionmentioning
confidence: 99%
“…If a greater number of cells are needed, a static or small-scale bioreactor seed train can be developed to increase the number of starting cells, and the surface area in the reactor can be increased by adding more microcarriers. We have previously shown that by starting with 12 million cells with a microcarrier density of 2 g/L, about 667 million cells can be generated before harvest [ 34 ]. Using the overall harvesting efficiency determined in this study, by increasing the starting cell number by 4-fold we can generate an estimated 500 million cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that both these schemes of fed‐batch operation resulted in better performance as compared to the batch operation. Further comparison of N=4 case and N=4O2 case by considering one more control variable as oxygen was also made as oxygen significantly affects cell growth (Hu & Bentley, 1999; Oliveira et al, 2005; Walsh et al, 2021). Here, the result shows that though the IGD value for N=4O2 was higher that N=4 case, the performance was similar in both cases in terms of the final virus and cell density obtained.…”
Section: Discussionmentioning
confidence: 99%